Effect of Work Life Balance & Antecedent Variable on Intention to Stay (A Study of Female Employees in High Performing Banks in Jakarta) - Purba, Sylvia (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This research raised a topic about Work-Life Balance (WLB) and the antecedent variable towards Intention to Stay. This study was conducted on 154 female respondents who worked as bank employees in the best performing banks in Jakarta by purposive sampling method as married women whose have children and has been working more than 3 years. WLB which stated in respondent perception found that is positively influenced towards Intention to Stay, where Management of Dual Role and The Organizational Support Practices is the antecedent variable of WLB. Consequently, Management of Dual Role in fact is not influenced towards Intention to Stay meanwhile The Organizational Support Practices still influenced 10 % of Alpha. The interesting finding in this research known that WLB influenced by Management of Dual Role used house-maid service and The Organizational Support Practices have not touched the support towards Dual Role Women. It is described that the organization has not been supported the WLB issue.